Determinants of Students’ Learning Outcomes in Vocational Blended Learning Environments: Evidence from PLS-SEM Analysis - Zouyan; Ida Bagus Putu Arnyana (Universitas Pendidikan Ganesha, 2025)
The education sector has undergone significant transformation with the increasing adoption of blended learning models. Nevertheless, challenges remain in ensuring that blended learning implementation effectively enhances students’ learning outcomes, particularly in vocational education, which is characterized by practical and skill-oriented learning. This study aims to analyze the implementation of blended learning models on online education platforms and to examine the factors influencing students’ learning outcomes. The study employed a quantitative approach grounded in the positivist paradigm. The research participants consisted of 381 vocational education students in Beijing selected through random sampling. Data were collected using structured Likert-scale questionnaires measuring several key constructs, including perceived usefulness, perceived ease of use, subjective norms, attitudes toward use, behavioral intention, prior experience, and students’ learning outcomes. Data analysis was conducted using descriptive statistics and inferential analysis through linear regression and Partial Least Squares–Structural Equation Modeling (PLS-SEM), supported by SPSS and SmartPLS software. The results indicate that perceived usefulness, perceived ease of use, and prior experience have significant positive effects on students’ learning outcomes. Attitudes and behavioral intention function as mediating variables that strengthen the relationship between students’ perceptions and learning outcomes, while prior experience serves as a moderating variable. This study concludes that effectively designed blended learning, supported by positive attitudes and students’ digital experience, can significantly enhance learning outcomes in vocational education.